KEPATUHAN IBU HAMIL DALAM MELAKUKAN PEMERIKSAAN KEHAMILAN DI DESA SIDOREJO, KECAMATAN PULOKULON, KABUPATEN GROBOGAN - Dary; Arwyn W. Nusawakan; Fitria Setyaningrum (MEDIA ILMU KESEHATAN, 2017)
Background: Maternal health has become one barometer of achievement of a country, especially developing countries like Indonesia. AKI Indonesia is 359 per 100,000 live births, not in accordance with MDGs target in 2015 that is 102 deaths per 100,000 live births. One of the causes of high AKI is because mothers do not utilize Antenatal Care (ANC) visit. Antenatal Care (ANC) is a professional health service (doctors specialist, general practitioner, midwife, and nurse) for the mother during her pregnancy in accordance with antenatal care standards. Objective: The purpose of this research is to know factors related to maternity compliance in performing pregnancy examination and to correlate each factor with the compliance. Methods: Sample of this quantitative study was mother who experienced pregnancy and has child younger than 3 year old living in Sidorejo village. 30 samples were recruited and then asked to fill in questionnaire. The data were analysed by using Correlation Spearman. Results: Very weak relationship between 7 maternal attributes with their obedience regarding examination of pregnancy found in this study namely age 0.030, employment 0.067, health insurance ownership 0.089, parity 0.017, history of pregnancy examination 0.019, Family support 0.083, and culture -0.098, while incomes 0.247 and knowledge 0.222 attributes indicate weak relationship level. Conclusion:There are relationships weak and very weak between the ages of , work , income , ownership health insurance , of parity , the acts of examination pregnancy , knowledge , family encouragement , culture and compliance mother in melakkan anc Keywords: Antenatal care, adherence